Minskande andelar kraftfoder i foderstaten under betesperioden : effekt på mjölkavkastning och betesbeteende hos mjölkkor - Alvåsen, Karin (SLU/Dept. of Animal Nutrition and Management (until 231231), 2009)
Feed costs constitute a large part of the expenses of dairy farmers. Pasture is a high quality feed with a low cost. However, feeding with concentrates has been shown to enhance milk yield (Leaver, 1985; Bargo et al., 2003; Stockdale, 2004). The purpose with this study was to investigate how milk yield and milk composition were affected as the concentrate proportion in the diet decreased. Pasture behaviour was examined to see if the different concentrate levels affected the time cows spent grazing and ruminating. Since ruminating animals give rise to methane emissions, methane emissions from the different feed ratios were estimated using equations obtained from the literature.